Parametric study and multiple correlations of an H-type finned tube bank in a fully developed region. (2nd July 2016) - Jin, Yu; Yu, Zhi-Qiang; Tang, Gui-Hua; He, Ya-Ling; Tao, Wen-Quan
ABSTRACT: The air-side heat transfer and pressure drop characteristics of an H-type finned tube bank in the turbulent periodically fully developed region are investigated numerically. The effects of seven geometric parameters and Reynolds number are examined. It is found that when the number of tube rows is equal to and larger than 25, the heat transfer and fluid flow approach the fully developed state. Among the seven geometric parameters spanwise tube pitch has the most important effect. Based on the numerical results, the correlations of heat transfer and pressure drop of the H-type finned tube bank for the fully developed region are presented.